THE IMPORTANCE OF USING A “CLIL” METHOD IN TEACHING A FOREIGN LANGUAGE - A. Rsaliev; Juraeva Shakhnoza Kamoliddin qizi (Western European Studies, 2024)
This article provides a teaching method of the CLIL (Content and Language Integrated Learning). CLIL is widely spread in European countries, for learning content trough an additional language (foreign or second) as a consequence of teaching both the language and the subject. In this methodology utilized in bilingual programs, particularly in science education, that provides student not only with communicative and linguistic benefits, however additionally, incorporating subject matter expertise with Content and Language Integrated Learning, which pertains to the acquisition of English language skills
Keywords: CLIL; English language; European countries